Fivefold twin formation during annealing of nanocrystalline Cu - Bringa, Eduardo Marcial (2008)
Contrary to the common belief that many-fold twins in nanophase materials are due to the action of significant external stresses, we report molecular dynamics simulations of 5 nm grain size Cu samples annealed at 800 K showing the formation of fivefold twins with no external pressure. The structure of the many-fold twins is remarkably similar to those we have found to occur under uniaxial shock loading in nanocrystalline NiW. The formation mechanism of the many-fold twins is discussed.